2014
DOI: 10.5392/jkca.2014.14.03.259
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between High School Students' Experience of Visiting the Dental Clinic and Oral Symptoms

Abstract: The purpose of this study is to investigate correlation between experience of visiting the dentist and oral symptoms with 10,701 high school seniors in the research data of the 8th juvenile online health behavior carried out in 2012. The results of this research showed that the lower academic grades, the more tooth crack they experienced, and the lower economic conditions, the more toothache they tended to experience. The main reasons they visited the dentist were because their teeth ached, tingled or throbbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This study surveyed self-report of oral disease symptoms without assessing actual disease appearance. However, multiple studies have used self-reported oral symptoms as a reliable marker for actual disease appearance [ 25 – 27 ]. Therefore, it is plausible to suggest that the association between sleep duration and oral symptom experience (dental pain and hemorrhage) defined in this study is comparable to the literature results elaborated above.…”
Section: Discussionmentioning
confidence: 99%
“…This study surveyed self-report of oral disease symptoms without assessing actual disease appearance. However, multiple studies have used self-reported oral symptoms as a reliable marker for actual disease appearance [ 25 – 27 ]. Therefore, it is plausible to suggest that the association between sleep duration and oral symptom experience (dental pain and hemorrhage) defined in this study is comparable to the literature results elaborated above.…”
Section: Discussionmentioning
confidence: 99%